(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Kinetics of CO oxidation on Cu-Co-Fe oxide catalysts supported on carbon nanotubes is investigated and it is shown, that the kinetic experimental data are submitted to the Eley-Readil mechanism in good agreement with bulk Cu-Co-Fe oxide catalysts. The data of activation energy for CO oxidation was determined for this catalyst.